COVERAGE AND FACTORS ASSOCIATED WITH TETANUS TOXOID VACCINATION AMONG MARRIED WOMEN OF REPRODUCTIVE AGE: A CROSS SECTIONAL STUDY IN PESHAWAR - Naeem, Mohammad; Khan, Muhammad Zia-Ul-Islam; Abbas, Syed Hussain; Adil, Muhammad; Khan, Ayasha; Naz, Syeda Maria; Khan, Muhammad Usman (Journal of Ayub Medical College Abbottabad, 2010)
Background: Pakistan has one of the highest maternal mortality rates in the world, with widely prevalent maternal and neonatal tetanus. The purpose of this study was to estimate the coverage and determine the factors associated with tetanus toxoid vaccination status among females of reproductive age in Peshawar. Methods: A Cross-sectional study was conducted in Peshawar, Pakistan, from 9 June to 19 June 2010. A total of 304 females of reproductive age (17-45) years were selected from both urban and rural areas of Peshawar through random sampling. A pre-tested structured questionnaire was administered to females. Questions about demographics, income, education of husband, occupation, accessibility to health centres and frequency of visits from health workers was inquired. Knowledge and views on immunization were also asked. Results: Overall 55.6% were vaccinated. Urban population was 54.3% while rural population was 45.7%. Reasons for not vaccinating were: No awareness (38.4%), being busy (18.1%), centre too far (18.1%), misconceptions (10.86%), and fear of reactions (4.3%). Most of the females thought immunization was effective (89.5%). Husband education, females’ knowledge and views on immunization, income, distance, frequency of health visits were the main factors associated with immunization status. Conclusion: Majority of females are not vaccinated. Effective media campaigns on maternal tetanus vaccination should be carried. Lady health workers should be mobilised effectively to increase the vaccination coverage. Keywords: Tetanus toxoid, immunization, EPI Pakistan